Seroprevalence of hantavirus infection in non-epidemic settings over four decades: a systematic review and meta-analysis - Fernando Tortosa; Fernando Perre; Celia Tognetti; Lucia Lossetti; Gabriela Carrasco; German Guaresti; Ayelén Iglesias; Yesica Espasandin; Ariel Izcovich (BMC, 2024)
Abstract Introduction Hantavirus infection is a zoonotic disease from rodents to humans, necessitating seroprevalence assessment for disease burden clarification and control measure implementation. This study aimed to estimate global hantaviruses seroprevalence, examining variations by regions, populations or settings. Methods A comprehensive database search identified studies on human hantaviruses seroprevalence using IgG detection until january 2024. A random-effects meta-analysis estimated pooled seroprevalence, with subgroup analyses for geographical region, population, setting or occupation. Results Out of 3,382 abstracts reviewed, 110 studies were selected, comprising 81,815 observations and 3207 events. The global seroprevalence was calculated at 2.93% (2.34%-3.67%). In terms of geographical distribution, our analysis encompassed 61 studies from the Americas, where the seroprevalence was estimated at 2.43% (95% CI: 1.71%-3.46%), 33 studies from Europe indicating a seroprevalence of 2.98% (95% CI: 2.19%-4.06%), 10 studies from Asia revealing a seroprevalence of 6.84% (95% CI: 3.64%-12.50%), and 6 studies from Africa demonstrating a seroprevalence of 2.21% (95% CI: 1.82%-2.71%). Subgroup analysis underscored varying seroprevalence rates across different populations, settings, and occupations, highlighting the necessity for targeted interventions and preventive measures. Conclusion The analysis reveals a moderate global hantaviruses seroprevalence, emphasizing the viral family's complex transmission dynamics influenced by exposure and geographical factors. This highlights the need for targeted prevention and control strategies.